2019
DOI: 10.2196/12358
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Care Monitoring and Data Collection Tool (H3 Tracker) to Assess Uptake and Engagement in Mental Health Care Services in a Community-Based Pediatric Integrated Care Model: Longitudinal Cohort Study

Abstract: Background National recommendations for pediatric integrated care models include improved capacity for care coordination and communication across primary care and specialty mental health providers using technology, yet few practical, short-term solutions are available for low-resource, community-based pediatric integrated care clinics. Objective The goal of the paper is to describe the development and features of a Web-based tool designed for program ev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Technology has been recognized as important for the optimal functioning of the CoCM from an early stage. For example, clinicians and researchers recognized the necessity of using caseload registries to manage patient information, track outcomes, and have easy access to information from assessments and follow-up appointments [28][29][30][31][32]. In addition, telephoneand 2-way video-based remote care emerged in the 2000s as a viable method of providing CC [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Technology has been recognized as important for the optimal functioning of the CoCM from an early stage. For example, clinicians and researchers recognized the necessity of using caseload registries to manage patient information, track outcomes, and have easy access to information from assessments and follow-up appointments [28][29][30][31][32]. In addition, telephoneand 2-way video-based remote care emerged in the 2000s as a viable method of providing CC [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…When children were identified as being in need of mental health services, either by a positive PSC score or by referral, they were introduced to the on-site study coordinator who confirmed eligibility, obtained informed consent, and completed study enrollment. The child and caregiver then completed the baseline survey using a web-based data capture system (McCreary et al, 2019). The University of California, Los Angeles and the University of Illinois at Chicago Institutional Review Boards approved this study.…”
Section: Methodsmentioning
confidence: 99%
“…Technology has been recognized as important for the optimal functioning of the CoCM from an early stage. For example, clinicians and researchers recognized the necessity of using caseload registries to manage patient information, track outcomes, and have easy access to information from assessments and follow-up appointments [28][29][30][31][32]. In addition, telephoneand 2-way video-based remote care emerged in the 2000s as a viable method of providing CC [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%